A single-center study of bone mineral density in adult patients with severe hemophilia A in correlation with markers of bone metabolism - Ivanova, Hristina A.; Grudeva-Popova, Zhanet; Deneva, Tanya; Tsvetkova, Silvia; Mateva, Nonka (Folia Medica, 2023)
Introduction: Osteopenia and osteoporosis are well-known hemophilia A comorbidities. The pathogenesis of bone turnover alteration resulting in reduced bone mass includes impaired osteoblastic differentiation and disinhibition of RANKL-induced osteoclastogenesis as a result of a low FVIII level. Aim: To evaluate the bone mineral density (BMD) in adult patients with severe hemophilia A and assess a possible correlation with the bone remodeling biomarkers OPG/RANKL, CTX-1, osteocalcin, and Vit D. Materials and methods: 28 male subjects with severe hemophilia A and 33 age-matched controls were recruited. The biomarkers were tested with the ELISA assay and BMD with DEXA of the lumbar spine (LS) and total hip (TH). Results: The patients had lower LS-BMD (−0.955±0.145 vs. 1.118±0.079, p=0.05) and TH-BMD (−0.840±0.147 vs. 0.951±0.075, p=0.05) than those of the controls. The TH T-scores were −1.41±0.91 vs. 0.4±0.49 (p=0.05) and the LS T-scores −1.16±1.046 vs. 0.14±0.72 (p=0.05). 66.6% of patients under 50 years had osteopenia and 8.3% had osteoporosis. Fifty percent of those over 50 years old had osteopenia and 20% had osteoporosis. We found significantly higher OPG levels (123.69±107.05 vs. 41.98±18.95, p=0.05) than that in controls and lower sRANKL levels (23.49±29.39 vs. 131.32±201.27, p=0.05) and sRANKL/OPG ratio (0.27±0.35 vs. 5.28±10.01, p=0.05) than those in controls. A positive correlation was found between sRANKL and the BMD T-score of lumbar spine (p=0.001) in the patient group. Conclusions: sRANKL level and ratio can be used as predictors of low BMD.